Acute Myocardial Infarction in Young Adults: Study of Risk factors, Angiographic Features and Clinical Outcome - Tamrakar, Rikesh; Bhatt, Yadav Deo; Kansakar, Subodh; Bhattarai, Mahesh; Shaha, Kunal Bikram; Tuladhar, Eanstara (Nepalese Heart Journal, 2014)
Background and aims: Acute myocardial infarction below 45 years of age constitutes a specific subset of population having different risk factors and clinical features as compared to older patients. Pattern of coronary artery involvement and clinical outcome also varies suggesting different underlying pathophysiology. Better understanding this specific problem will lead to further improvement in management. Methods: One hundred and fifteen consecutive patients diagnosed as acute myocardial infarction and were below 45 years over the period of one year were enrolled in the study. Clinical parameters, risk factors, angiographic patterns were analysed. Patients were assessed daily during hospital stay to study in-hospital outcome and complications. Results: Out of total patients studied, 64.3% were smokers, 27.8% were hypertensive, 15.65% were diabetic and 9.6% had history of dyslipidemia. There was history of recreational drug abuse in 4.3% of patients. Most patients present as ST elevation myocardial infarction (87%). Majority of patients were in Killip class I (69.5%) at presentation in emergency. Single vessel disease (58.3%) was the most common finding in coronary angiography and 7.6% patients have normal or non obstructive coronary lesions. Complications include arrhythmia (6%), cardiogenic shock (5.2%) and mortality (1.7%). Conclusions: In young acute myocardial infarction patients, smoking is the single most important modifiable risk factor. Other conventional risk factors are less strongly associated than older patients. Young patients tend to have less extensive coronary artery lesions. In few patients, presence of normal or non obstructive coronary lesions would suggest possibility of different mechanism of myocardial necrosis. Overall, these patients had favourable outcome and better prognosis. Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 12-16 DOI: http://dx.doi.org/10.3126/njh.v10i1.9740